Discovering immunoreceptor coupling and organization motifs - Reth, Michael (Frontiers in Immunology, 2023)
The recently determined cryo-EM structures of the T cell antigen receptor (TCR) and B cell antigen receptor (BCR) show in molecular details the interactions of the ligand-binding part with the signaling subunits but they do not reveal the signaling mechanism of these antigen receptors. Without knowing the molecular basis of antigen sensing by these receptors, a rational design of optimal vaccines is not possible. The existence of conserved amino acids (AAs) that are not involved in the subunit interaction suggests that antigen receptors form higher complexes and/or have lateral interactors that control their activity. Here, I describe evolutionary conserved leucine zipper (LZ) motifs within the transmembrane domains (TMD) of antigen and coreceptor components that are likely to be involved in the oligomerization and lateral interaction of antigen receptor complexes on T and B cells. These immunoreceptor coupling and organization motifs (ICOMs) are also found within the TMDs of other important receptor types and viral envelope proteins. This discovery suggests that antigen receptors do not function as isolated entities but rather as part of an ICOM-based interactome that controls their nanoscale organization on resting cells and their dynamic remodeling on activated lymphocytes.